Outcomes and Toxicities of Definitive Radiation and Reirradiation Using 3D Conformal or Intensity-Modulated (Pencil Beam) Proton Therapy for Nasal Cavity and Paranasal Sinus Malignances - Fan, Ming (Cancer, 2020)
BACKGROUND: Proton therapy (PT) improves outcomes in nasal cavity (NC) and paranasal sinus (PNS) cancers. We present the largest series utilizing intensity-modulated proton therapy (IMPT) in their treatment. METHODS: Between 2013 and 2018, 86 consecutive patients (68 radiation-naive and 18 re-irradiation) received PT to median doses 70Gy and 67Gy RBE, respectively. 53% received IMPT. RESULTS: Median follow-up was 23.4 months [1.7–69.3] for all and 28.1 months [2.3–69.3] for surviving patients. Two-year local control (LC), distant control (DC), disease-free survival (DFS), and overall survival (OS) were 83%, 84%, 72%, and 81% for radiation-naïve and 77%, 80%, 54%, and 66% for reirradiation patients. For radiation-naïve patients, compared to 3D conformal proton technique (3DCPT), IMPT significantly improved LC (91% vs. 72%, p<0.01), and independently predicted LC (HR 0.14, p=0.01). Sixteen radiation-naïve patients (24%) experienced acute grade 3 toxicities; three (4%) experienced late grade 3 toxicities (osteoradionecrosis, vision loss, soft tissue necrosis). Similar LC was seen for re-irradiation patients with higher complications, 11% experienced late grade 3 toxicities (facial pain, brain necrosis). Reirradiation patients had more Grade 1–2 radionecrosis than radiation-naïve patients (brain: 33% vs. 7%, osteoradionecrosis: 17% vs. 4%). CONCLUSIONS: PT achieved excellent LC for NC and PNS cancers with lower grade 3 toxicities relative to historical reports. IMPT has promise to improve the therapeutic ratio in these malignancies and is worthy of further investigation.